Assessment of Rice and Maize Based Cropping Systems For Rural Livelihood Improvement in Nepal - Pandey, Pradyumna Raj; Pandey, Hemprabha; Nakagawa, Mitsuhiro (Journal of Agriculture and Environment, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> This paper explores the assessment of rice and maize base cropping system in agro-ecological regions for sustainable rural livelihood development in Nepal. Analysis of 1994-2007 data showed rice-dominated cropping systems in the Plain region, as opposed to maize-dominated cropping systems in the Mountain and the Hill regions. The production increase was achieved mainly through increases in area. The growth in the yield of crops was very minimal in all three regions. During the last fifteen years, the cropping pattern changed slightly from Maize-Wheat to Maize-Paddy in the Mountain region, but no significant change was observed in the other two regions. The current rate of fertilizer application is lower than the recommended rate. Improved access to and availability of agricultural inputs is key to improve the production and yield of major food crops to achieve sustainable rural livelihood in the country. Key words: Agro-ecological-region; Cropping system; Farm income; Rural livelihood; sustainable livelihood The Journal of Agriculture and Environment Vol:10, Jun.2009 page: 67-75